2021
DOI: 10.1186/s12873-021-00401-x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of serum D-dimer assays prior to computed tomography pulmonary angiography scans in the diagnosis of pulmonary embolism among emergency department physicians: a retrospective observational study

Abstract: Background A variety of evidence-based algorithms and decision rules using D-Dimer testing have been proposed as instruments to allow physicians to safely rule out a pulmonary embolism (PE) in low-risk patients. Objective To describe the prevalence of D-Dimer utilization among emergency department (ED) physicians and its impact on positive yields and utilization rates of Computed Tomography Pulmonary Angiography (CTPA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In an article by Kruger et al, it was reported that a low or moderate clinical probability, combined with a normal D-dimer level, can rule out PE ( 4 ). A study by Salehi et al provided evidence of suboptimal adherence to CTPA abandonment in patients who tested D-dimer-negative before CTPA was performed ( 5 ). Yang et al observed that older age (increasing every 10 years), delay from the time of injury to surgery (daily), and fibrinogen levels > 0.…”
Section: Discussionmentioning
confidence: 99%
“…In an article by Kruger et al, it was reported that a low or moderate clinical probability, combined with a normal D-dimer level, can rule out PE ( 4 ). A study by Salehi et al provided evidence of suboptimal adherence to CTPA abandonment in patients who tested D-dimer-negative before CTPA was performed ( 5 ). Yang et al observed that older age (increasing every 10 years), delay from the time of injury to surgery (daily), and fibrinogen levels > 0.…”
Section: Discussionmentioning
confidence: 99%
“…A significant percentage of patients who were considered to be of a low CP of PE by both independent reviewers using Well's score, the YEARS algorithm, and the revised Geneva score were subjected to CTPA (61.4%, 55%, and 20.1%, respectively), and D-dimer testing was conducted in less than half of low-CP patients. Underutilization of the validated diagnostic predictive tools and D-dimer and overuse of CTPA are common in clinical practice [22][23][24]. Retrospective studies have reported the use of a clinical predictive tool in only 15-60% of patients with suspected PE [22,23,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…However, the d-dimer test showed a sensitivity of 95.7% and a specificity of 40% [ 1 , 16 ]. Another study that aimed to estimate the prevalence of d-dimer utilization in the ER revealed that there was a lack of adherence to the guidelines in terms of d-dimer testing before imaging with CT pulmonary angiography [ 17 ].…”
Section: Discussionmentioning
confidence: 99%